A goodwill shield for crisis communication: Exploring the ‘Halo Effect’ of CSR activities - Page, Tyler G.; Lin, Carolyn A. (Public relations review, 2025)
Corporate social responsibility is a corporate citizenship component that can serve as a goodwill shield to help protect organizational reputation in a crisis. How this good will shield functions to influence audience evaluation of corporate reputation, which often balances moral judgment and the nature of the offense, is not well-understood. As research addressing CSR and crisis management remains limited, this study explored this complex process with a between-subjects experiment regarding a fictional company. Participants were given introductory information about the company and asked to rate how they perceived the CSR of the fictional company. Next, participants were shown a crisis about the story and responded to measures of perceived crisis offensiveness, virtuousness, and then reputation of the company. Findings demonstrated that pre-crisis CSR perception had a significant halo effect on post-crisis perceptions of company reputation——as mediated by perceived virtuousness and crisis offensiveness—instead of a direct carryover effect. •The effect of perceived CSR on post-crisis reputation is tested in an experiment.•The halo effect is tested against a carryover effect.•Perceived CSR has a positive halo effect on post-crisis reputation that is mediated through virtuousness.•No significant carryover effect was discovered in this research.•The revised model of reputation repair is utilized to examine how perceptions of crisis influence post-crisis reputation.